2007
DOI: 10.1254/jphs.fp0070643
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of the Phosphoinositide 3-Kinase Inhibitor LY294002 on Muscarinic Acetylcholine Receptor-Induced Calcium Entry in PC12h Cells

Abstract: Abstract. Phosphoinositide-3 kinase (PI3K) and phospholipase C (PLC) utilize the same phosphoinositides as substrates to produce different signaling molecules. These enzymes are activated by a similar set of cell signaling mechanisms, i.e., tyrosine kinases and G proteins, and affect common cell functions, including proliferation, motility, and intracellular trafficking. Despite these similarities, the interplay between these enzymes is not well understood. To address this issue, the effects of the PI3K inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…LY294002 was identified as not being exclusively selective toward the PI3K inhibitor, but as inhibiting non-lipid kinases, such as casein kinase (CK)2, mammalian target of rapamycin (mTOR), and glycogen synthase kinase 3 (GSK) [36,37]. It also has additional novel targets that are unrelated to the PI3K family or kinases; for example, it acts directly on the human Kv 1.5 channel as an open channel blocker [38] and blocks calcium entry channels in PC12 cells [39]. Moreover, by binding directly to the estrogen receptor, LY294002 inhibits the 17β-estradiol-induced transcriptional activity of an estrogen-sensitive reporter gene [40].…”
Section: Discussionmentioning
confidence: 99%
“…LY294002 was identified as not being exclusively selective toward the PI3K inhibitor, but as inhibiting non-lipid kinases, such as casein kinase (CK)2, mammalian target of rapamycin (mTOR), and glycogen synthase kinase 3 (GSK) [36,37]. It also has additional novel targets that are unrelated to the PI3K family or kinases; for example, it acts directly on the human Kv 1.5 channel as an open channel blocker [38] and blocks calcium entry channels in PC12 cells [39]. Moreover, by binding directly to the estrogen receptor, LY294002 inhibits the 17β-estradiol-induced transcriptional activity of an estrogen-sensitive reporter gene [40].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the M 2 subtype also enhances the voltage-gated Ca 2+ channel current through PI3K in myocytes (Callaghan et al, 2004). Conversely, inhibition of the PI3K with LY294002 reduces mAChR-induced Ca 2+ influx in PC12 cells (Morita et al, 2007). In this study, we found that inhibition of PI3K with two structurally dissimilar inhibitors, wortmannin and LY294002, completely blocked the effect of oxotremorine-M on the frequency of sIPSCs in 40-48% neurons.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are activated by a similar set of cell signaling mechanisms, i.e., tyrosine kinases and G proteins, and affect common cell functions, including proliferation, motility, and intracellular trafficking [37]. LY294002 is a structurally distinct PI3K inhibitor that suppresses the activity of this kinase through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%